2019
DOI: 10.1111/dth.13037
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of frontal fibrosing alopecia with alitretinoin

Abstract: Frontal fibrosing alopecia (FFA) is an inflammatory disorder characterized by scarring alopecia of the frontotemporal scalp, thinning or loss of facial hair, and facial papules. Prompt treatment is essential to prevent permanent hair loss. Although studies have reported the efficacy of oral retinoids (isotretinoin and acitretin) in FFA treatment, a therapeutic role for alitretinoin is known only for lichen planus and not for FFA. Herein, we report a case of FFA accompanied with lichen planus that responded wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…A retrospective analysis of 54 women with FFA treated with oral isotreinoin (20 mg/day), acitretin (20 mg/day), or finasteride (5 mg/day) showed a stoppage of progression in 76%, 73%, and 43% of patients, respectively [ 197 ]. Alitretinoin has also been used in a woman with FFA, who showed improvement after one month with 30 mg/day [ 198 ].…”
Section: Treatmentmentioning
confidence: 99%
“…A retrospective analysis of 54 women with FFA treated with oral isotreinoin (20 mg/day), acitretin (20 mg/day), or finasteride (5 mg/day) showed a stoppage of progression in 76%, 73%, and 43% of patients, respectively [ 197 ]. Alitretinoin has also been used in a woman with FFA, who showed improvement after one month with 30 mg/day [ 198 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Retinoic acid has been reported to be effective as a topical treatment in OLP [52,53]. Oral treatment of tretinoin (a generic name of Vitinoin) has been reported to be effective in treating LP [36]. In Supplementary Table 2_C, we provide enrichment analysis results pertaining to drug terms within DSigDB In Figure 7, two subgraphs obtained from PPI networks are shown, including the following 25 genes:…”
Section: Methods Rank Term Overlap P-valuementioning
confidence: 99%
“…Table 4 shows retrieved terms pertaining to drugs associated with provided genes. The first term is for the drug Alitretinoin, which has been shown to be clinically effective in the treatment of LP cases [36,37]. The 2nd-ranked drug was Vitinoin, the generic name of which is tretinoin, which has been included in clinical trials and has demonstrated potential improvements in the clinical treatments pertaining to LP [38,39].…”
Section: Tablementioning
confidence: 99%
“…Frontal fibrosing alopecia (FFA) is an irreversible scarring cicatricial alopecia, manifesting as atrophic and band‐like recession of symmetric fronto‐temporal and fronto‐parietal hairline. FFA has been reported mainly in premenopausal women and rarely in men 1‐5 . It is considered a variant of lichen planopilaris (LPP) and is frequently associated with the presence of perifollicular erythema and scaling in the affected area.…”
Section: Introductionmentioning
confidence: 99%
“…FFA has been reported mainly in premenopausal women and rarely in men. [1][2][3][4][5] It is considered a variant of lichen planopilaris (LPP) and is frequently associated with the presence of perifollicular erythema and scaling in the affected area. The pathogenesis of FFA is poorly understood.…”
Section: Introductionmentioning
confidence: 99%